Disparities in Contemporary Treatment Rates of Abdominal Aortic Aneurysms Across Western Countries. (August 2019) - Castro-Ferreira, Ricardo; Lachat, Mario; Schneider, Peter A.; Freitas, Alberto; Leite-Moreira, Adelino; Sampaio, Sérgio M.
Abstract : Objective/background: Several abdominal aortic aneurysm (AAA) screening programs have demonstrated a similar prevalence of this disease in Westerns countries, ranging from 1.2% to 2.8%. However, the annual rate of AAA repair is significantly less even, and its relationship to AAA prevalence is not clear. The objective was to perform a systematic review, describing an international overview in the yearly rate of AAA repairs. Methods: The number of elective and emergency AAA repairs was obtained via thorough review of publications indexed in PubMed and Scopus from 2010 to October 2018. Portuguese data were obtained from the national administrative database of health care. Data from the UK were extracted from the National Vascular Registry's 2015 annual report. Each country's population was assessed from published national censuses, thus allowing estimation of the number of AAAs treated per 100, 000 habitants. Results: Data from 14 countries were obtained. The yearly number of elective operations per 100, 000 habitants was 2.2 in Hungary, 3.8 in Portugal, 5.3 in Spain, 5.9 in Iceland, 6.5 in Finland, 7.0 in New Zealand, 7.8 in the UK, 10.0 in Denmark, 10.2 in Sweden, 13.3 in the USA, 14.8 in Norway, 15.3 in the Netherlands, 15.6 in Italy, and 17.3 in Germany. The yearly rate of ruptured repairs was 0.5 in Hungary, 1.5 in Portugal, 1.8 in Spain, 1.7 in Iceland, 1.7 in Finland, 1.3 in New Zealand, 1.8 in the UK, 3.3 in Denmark (2013), 2.7 in Sweden (2013), 1.7 in the USA, 2.1 in Norway, 3.1 in the Netherlands, 2.3 in Italy, and 2.7 in Germany. Conclusion: The rate of AAA treatment is highly variable, with a nearly eightfold variance between the countries with the highest and lowest rates of elective repair. Correlation between elective and ruptured repairs was not clear. A deeper understanding of the reasons for the disparities in AAA treatment among Western countries is of the utmost importance.